THE EFFICIENCY OF PREPARED BIOFERTILIZER FROM LOCAL ISOLATE OF BRADYRHIZOBIUM SP ON GROWTH AND YIELD OF MUNGBEAN PLANT - Alkurtany, A. E. S.; Ali, S. A. M.; Mahdi, W. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Bradyrhizbium sp. was isolated from 40 legumes roots and soil samples collected from various agricultural areas of Iraq by growing them on yeast extract mannitol agar (YEMA) and identification based on culture and microscopic characteristics, biochemical and physiological test and PCR technology.  A split plot experiment was carried out to study the effect of biofertilizer prepared from this isolate on the growth and yield of mungbean plant in sterile and non-sterile soil. The results showed a significant increases in all studied growth and yield traits due to biofertilization. The increase percentage  for the biofertilized treatments was 159.35% and 266.66% compare to the non-fertilized treatments in the number and  dry weight of nodules,  respectively. The increase in dry weight of  root and vegetative part were 114.28% and 86.57% respectively , while the increase in the nitrogen concentration in the vegetative part was 16.94%. The results showed that the biofertilized treatment was significantly superior in number of plant pods, total yield and protein % in seeds compare with non-biofertilized, the percentage increase was 49.44%, 90.59% and 16.86% respectively. As for sterilization, the results showed no significant differences between sterilized and non-sterile soil in all growth and yield parameters of mungbean plant. The effect of interaction was significant, the biofertilized and sterilized treatment gave the highest value for all studied traits except the concentration of nitrogen in the vegetative part.